Development of two portable patternators to improve drift control and operator training in the operation of vineyard sprayers - Gil, E.; Landers, A.; Gallart, M.; Llorens, J. (Spanish Journal of Agricultural Research, 2013)
Spray drift can be defined as the quantity of plant protection product that is carried out of the sprayed area by the action of air currents during the application process. Efficacy of pesticide applications in orchards and vineyards is highly dependent on matching the canopy characteristics with the liquid distribution on a vertical plane, this being influenced by the type of sprayer, the nozzle orientation and air outlet adjustment. Two simple vertical patternators were designed and developed with the express purpose to be used in field conditions for the adjustment of vineyard canopy sprayers. Three different orchard sprayers were selected for comparative field trials of two new patternators with an already commercially available portable vertical patternator designed at University of Turin (Italy). The objective was to evaluate their efficiency in terms of spray recovery, symmetry and repeatability. Results show the ability of the two prototypes to measure the vertical distribution of liquid, as well as the important similarities between the liquid distribution profiles obtained with both patternators in comparison to the reference one. Trials conducted with the three different orchard sprayers show the suitability of this kind of tool, not only for research purposes but also for training activities and as part of the sprayer calibration process. Important benefits from both an economic and a sustainable point of view can be obtained regarding adequate liquid distribution according to the crop characteristics, this being especially interesting in field conditions.